Teachers’ efforts in fostering early childhood independence through life skills–based learning - Hanifah Samara; Sabrina Khairunnisa (Journal of Childhood and Elementary Studies, 2025)
childhood education, encompassing children’s ability to manage self-care, regulate emotions, take responsibility, and interact socially. The development of independence is strongly influenced by human factors, particularly teachers’ roles and daily pedagogical interactions. Life skills–based learning has been widely promoted as an effective approach to foster independence; however, empirical studies that explore teachers’ efforts and classroom practices from a human-centered perspective remain limited. Aims: This study aims to examine teachers’ efforts in fostering early childhood independence through life skills–based learning, with a focus on teacher–child interactions, learning activities, and independence-related behaviors. Method: This study employed a qualitative descriptive research design conducted at an early childhood education institution. Data were collected through classroom observations, semi-structured interviews with teachers, and documentation of learning activities. Data analysis was carried out through data reduction, data display, and conclusion drawing, supported by triangulation to enhance credibility. Results: The findings indicate that life skills–based learning contributes positively to children’s independence across physical, social, and emotional dimensions. Teachers supported independence through habituation, guided practice, role modeling, and motivational reinforcement. Most children demonstrated independence at the developed-as-expected level, although variations were observed across indicators such as discipline and self-confidence. Conclusion: Teachers play a central role in fostering early childhood independence through life skills–based learning. Human-centered pedagogical practices and consistent daily routines support the gradual development of autonomy. Strengthening collaboration between teachers and families is essential to optimize independence development in early childhood settings.